UJI BAKTERIOLOGIS AIR MINUM ISI ULANG DI PASIR PENGARAIAN KABUPATEN ROKAN HULU, RIAU - Rizwana Wahyuni, Rizah (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Water is an important thing to raise the people’s health level and clean water is alsoneeded for every living creature. That is why, it is important to know the quality of the wateritself. The purpose of this research is to test the quality of refill drinking water and to find outany filth can be found in that water based on Indonesia’s National Quality Standard (SNI). Themethod used in this research was saturated sample, where all the population of refill waterstation was treated as the samples. There were 21 samples in this research which was useddescriptive statistical analysis to display the result of this research. It is showed in the form oftable. Then, it was compared by the standard of SNI. The parameter of this research wascolifrom bactery. From the 21 samples were tested in the laboratory of National EnvironmentBoard in Pasir Pengaraian, there were only 6 samples which are fulfill the standard of SNI. Toovercome it, the owners can use the Ultra Violet (UV) shining process to eliminate thecolifrom bactery.Keywords : Colifrom,Drinking Water, Quality